Can college courses in prison cut crime after release? A review of follow-up studies of prison higher education and recidivism - Lockwood, Daniel (American journal of criminal justice, 1991)
This paper discusses empirical findings and theories about prison higher education and recidivism. The research designs of available evaluations of prison higher education are discussed. Their results in regard to arrest and return to prison after release are presented in tables and figures. Both opportunity theory and moral development theory have been used to justify such prison programs as crime prevention measures. A critical examination of the actual findings of the evaluations carried out up to now suggests that prison higher education may have had only a slight impact on recidivism. One could, therefore, doubt the value of opportunity theory and moral development theory to justify prison higher education as a crime control measure. However, the methods used in the evaluations of this program have been generally weak. Thus, there is a continuing need to carry out well-designed research on this question. The findings of follow-up studies of prison higher education have significance for issues of correctional education policy as well as criminological theory.